2022
DOI: 10.3389/fpubh.2022.941922
|View full text |Cite
|
Sign up to set email alerts
|

Association between environmental lead/cadmium co-exposure in drinking water and soil and type 2 diabetes mellitus/obesity in Southern China

Abstract: Lead (Pb) and cadmium (Cd) in environment can be directly absorbed by drinking water and soil. However, data on human Pb and Cd exposure by drinking water and soil and its long-term consequence for type 2 diabetes mellitus (T2DM) and obesity are lacking. Our study aims to explore the association of typical heavy metals co-exposure in drinking water and soil to the community residents with T2DM and obesity indices in two cities of southern China. A cross-sectional study enrolling total 1,274 participants was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Hence, it is important to construct a database of mortality-risk profiles for each racial or ethnic group. Regarding weight status, there is observational evidence that higher to lower lead concentrations were significantly associated with a lower likelihood of being overweight relative to normal weight ( 36 ). In other words, the detrimental impact of body lead in overweight or obese individuals was lower than that in underweight or normal-weight individuals, which may, at least in part, account for the significant association between urine lead and cancer-specific mortality in underweight or normal-weight adults.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important to construct a database of mortality-risk profiles for each racial or ethnic group. Regarding weight status, there is observational evidence that higher to lower lead concentrations were significantly associated with a lower likelihood of being overweight relative to normal weight ( 36 ). In other words, the detrimental impact of body lead in overweight or obese individuals was lower than that in underweight or normal-weight individuals, which may, at least in part, account for the significant association between urine lead and cancer-specific mortality in underweight or normal-weight adults.…”
Section: Discussionmentioning
confidence: 99%
“…One is that acute or chronic lead exposure does not destroy TC, but may reduce TC levels, which may be the reason why non obese individuals with high lead level have a higher risk of hypertension than obese individuals ( 55 , 56 ). The Other is that Pb exposure may damage the gastrointestinal function and lead to weight loss ( 57 ). In addition, Pb exposure can reduce the basal level of cortisol and possibly reduce the risk of obesity by destroying the hypothalamic-pituitary-adrenal axis ( 58 ), which is consistent with the negative interaction between lead and obesity found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the recent study, Zhong et al [ 61 ] found negative correlation between multimetal exposure and obesity, although they did not focused on the investigation of underlying molecular mechanisms. In other study, Qu et al [ 64 ] attempted to find out a link between Pb and Cd co‐exposure, and the obesity indicators such as BMI, waist‐to‐hip ratio, and waist circumference. The findings indicated that there was no significant association between obesity and individuals’ average daily dose of Pb and Cd.…”
Section: Multimetal Exposure‐associated Toxicity and Riskmentioning
confidence: 99%
“…The findings indicated that there was no significant association between obesity and individuals’ average daily dose of Pb and Cd. [ 64 ] The National Health and Nutrition Examination Survey conducted on US population during 2003–2014 suggested that obesity and its associated chronic conditions such as hypertension and type 2 diabetes are linked to cumulative exposure to the mixtures of heavy metals. [ 39 ]…”
Section: Multimetal Exposure‐associated Toxicity and Riskmentioning
confidence: 99%